Cutting-edge Strategies for Overcoming Therapeutic Barriers in Alzheimer's Disease - Inamdar, Aparna; Gurupadayya, Bannimath; Halagali, Prashant; S., Nandakumar; Pathak, Rashmi; Singh, Himalaya; Sharma, Himanshu (Current Pharmaceutical Design, 2025)
Alzheimer's disease (AD) remains one of the hardest neurodegenerative diseases to treat due to its enduring cognitive deterioration and memory loss. Despite extensive research, few viable treatment approaches have been found; these are mostly due to several barriers, such as the disease's complex biology, limited pharmaceutical efficacy, and the BBB. This presentation discusses current strategies for addressing these therapeutic barriers to enhance AD treatment. Innovative drug delivery methods including liposomes, exosomes, and nanoparticles may be able to pass the blood-brain barrier and allow medicine to enter specific brain regions. These innovative strategies of medicine distribution reduce systemic side effects by improving absorption. Moreover, the development of disease-modifying treatments that target tau protein tangles, amyloid-beta plaques, and neuroinflammation offers the chance to influence the course of the illness rather than only treat its symptoms. Furthermore, gene therapy and CRISPR-Cas9 technologies have surfaced as potentially ground-breaking methods for addressing the underlying genetic defects associated with AD. Furthermore, novel approaches to patient care may involve the utilization of existing medications having neuroprotective properties, such as those for diabetes and cardiovascular conditions. Furthermore, biomarker research and personalized medicine have made individualized therapy approaches possible, ensuring that patients receive the best care possible based on their unique genetic and molecular profiles.
Keywords: drug delivery systems